Hubungan Kualitas Pelayanan terhadap Kepuasaan Pelanggan pada Kantor Perusahaan Daerah Air Minum di Kota Sampit Kabupaten Kotawaringin Timur - Indah Tri Handayani; Fitri Marlita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
This study aims to find out and analyze how much the quality of service services relates to the level of satisfaction felt by customers who use the services of Regional Water Companies (PDAMs). The research method used in this study is the observation method, the questionnaire using the Likert scale and the process of determining the sample used is the level of error of 10% as much as 162 samples, the type of research used is associative quantitative that is to find the relationship between service quality and customer satisfaction Testing the hypothesis used is a statistical test with the formula